Enhanced production of butanol and xylosaccharides from Eucalyptus grandis wood using steam explosion in a semi-continuous pre-pilot reactor. (15th April 2021) - Cebreiros, Florencia; Risso, Florencia; Cagno, Matias; Cabrera, Maria Noel; Rochón, Eloísa; Jauregui, Guillermo; Boix, Elzeario; Böthig, Silvia; Ferrari, Mario Daniel; Lareo, Claudia
Highlights: 40% of eucalyptus initial xylan was recovered as xylosaccharide in liquid fraction. 76% glucan hydrolysis from pretreated solids to fermentable sugars was achieved. C. beijerinckii DSM 6422 produced 13 g/L of ABE from unwashed pretreated solid. Buffer selection was critical for IBE fermentation by C. beijerinckii DSM 6423. C. beijerinckii DSM 6423 produced 10 g/L of IBE from washed pretreated E. grandis . Abstract: In this work, the co-production of xylosaccharides and butanol from Eucalyptus grandis wood using steam explosion pretreatment in a biorefinery platform was investigated. The effect of different temperature conditions on xylosaccharide production and selectivity as well as enzymatic hydrolysis of pretreated E. grandis substrates was studied using a pre-pilot steam explosion reactor. Under selected conditions (200 °C, 1.5 MPa, 10 min), steam explosion pretreatment led to about 50% xylan recovery as xylooligosaccharides (XOS) and xylose and 80% glucan enzymatic hydrolysis even at high solid loading. A xylosaccharide-rich hydrolysate was effectively separated by ion-exchange and resin treatment, containing mostly xylose and xylobiose as XOS. The fermentation performance of four native butanol-producing strains ( Clostridium acetobutylicum DSM 1731, Clostridium beijerinckii DSM 6422, Clostridium beijerinckii DSM 6423 and Clostridium saccaroperbutylacetonicum DSM 14923) were evaluated using semi-synthetic media and enzymatic hydrolysates for butanol production. Results showed that ABE strain Clostridium beijerinckii DSM 6422 and IBE strain Clostridium beijerinckii DSM 6423 are robust native strains for butanol production from lignocellulosic materials. This work highlights a potential integrated biorefinery process for the efficient utilization of E. grandis wood to produce biofuels and biochemicals.